The Greetings of Romans 16 and the Audience of Romans - Head, P (Cambridge University Press, 2024)
This short paper considers and critiques the view that the named people greeted in Romans 16.3–16 are not also among the recipients of the letter to ‘all God's beloved in Rome’ (Rom 1.7). Variants of this view spring from the work of Mullins (1968): that the second-person greeting involves the greeting of ‘a third party who is not intended to be among the immediate readership of the letter’ (Mullins, 1968: 420) and are found in Thorsteinsson (2003), Stowers (2015) and Campbell (2023). A series of arguments are made against this view. In particular, the plural form of the imperative (ἀσπάσασθɛ) and the open nature of the addressees mean that Mullins' simple principle does not apply. In addition, Paul's usage elsewhere (including in Romans 16.16) contradicts Mullins' principle.